The real-world adherence of the first-line anti-osteoporosis medications in Taiwan: Visualize the gap between reality and expectations - Chia-Che Lee; Shau-Huai Fu; Ho-Min Chen; Jou-Wei Lin; Chih-Cheng Hsu; Sheng-Chieh Lin; Jawl-Shan Hwang; Rong-Sen Yang; Chih-Hsing Wu; Chen-Yu Wang (Journal of the Formosan Medical Association, 2023)
Background: Adherence to anti-osteoporosis medications (AOMs) is crucial. National Health Insurance (NHI) in Taiwan has its own rules of reimbursement rule for AOMs. The midterm adherence remained inconclusive. Here we investigated the adherence according to the initially used AOMs, for three consecutive years. Methods: The nationwide cohort study from 2008 to 2018, based on Taiwan's National Health Insurance Research Database, included 336,229 patients. Their adherence, indicated by medication possession ratio (MPR), to the initial AOMs was investigated yearly for three consecutive years. The overall MPRs (OMPR), including the switched AOMs, were also calculated in the first year. The Sankey diagram further visualized the patient flows toward different adherence according to the initial AOMs. Results: The OMPR in the first year improved if the patients used AOMs with longer dosing intervals. 100%, 68.9%, 40.7%, and 34.0% of the patients started the treatment with zoledronate, denosumab, alendronate, and raloxifene, respectively, had OMPR ≥75% in the first year. In the 3rd year, only 20.89%, 24.13%, and 12.83% of the patients continuously treated with zoledronate, denosumab, and alendronate, respectively, had MPR ≥75%. From the Sankey diagram, we also observed that patients who had poor adherence at one year were inclined to have poor adherence or discontinue antiosteoporosis treatment in the next year. Conclusion: The initial AOMs and the observed adherence may provide clues for optimizing patient treatment. The real-world adherence in Taiwan was far from satisfactory in our study.